Changes in choice evoked brain activations after a weight loss intervention in adolescents. (1st August 2016) - Mata, Fernanda; Verdejo-Roman, Juan; Soriano-Mas, Carles; Yücel, Murat; Verdejo-Garcia, Antonio
Abstract: This study was aimed to investigate if treatment-related success in weight loss (i.e., reductions of BMI and fat percentage) is linked to significant changes in choice evoked brain activity in adolescents with excess weight. Sixteen adolescents with excess weight (age range: 12–18; BMI range: 22–36) performed the Risky-Gains Task during functional Magnetic Resonance Imaging (fMRI) both before and after a 12-week weight loss intervention. Success in weight loss was selectively associated with increased activation in the anterior insula. We concluded that adolescents with the greatest increases in activation of the insula-related interoceptive neural circuitry also show greater reductions in BMI and fat mass.